Pemanfaatan Media Sosial sebagai Platform Inovatif dalam Pendidikan Agama Islam di Era Digital - Nur Azizah Zulkifli (Journal of Innovative and Creativity, 2025)
To explore the role of social media as an innovative tool in Islamic Religious Education learning in the global era. To identify the potential, challenges and strategies for implementing social media in supporting effective Islamic Religious Education learning that is relevant to current developments. This research method is qualitative literature research, with a descriptive approach, which is a way or procedure for solving research problems by describing the object being studied as it is. Data collection techniques used in this study are books and articles/journals. tool in Islamic Religious Education (PAI) learning in the global era. With its ability to present material creatively and interactively, social media helps bridge the gap between the needs of the digital generation and the essence of Islamic teachings. Social media facilitates the delivery of learning materials through various attractive formats, expands the scope of learning, and increases student collaboration and involvement. However, the use of social media also presents a number of challenges, such as content validity, interference, and the risk of technology addiction. Therefore, an appropriate strategy is needed, including improving digital literacy, managing screen time, and providing clear guidance on the use of social media. This study enriches the theory of the use of digital technology, especially social media, in religious learning. And this can be a basis for developing new theories about the integration of technology in education based on spiritual values. The results of this study indicate the need for training for teachers to be able to use social media effectively in Islamic Religious Education learning, including in filtering appropriate and useful content.